ANALISIS YURIDIS PEMBUATAN AKTA ELEKTRONIK OLEH PPAT DALAM PERSPEKTIF PP 18/2021: PELUANG, TANTANGAN, DAN IMPLIKASI TERHADAP KEPASTIAN HUKUM - Adelina, Alda Anabela; Sendrawan, Tjhong (Jurnal Ilmiah Advokasi, 2025)
Article 86 of Government Regulation (PP) No. 18 of 2021 opens opportunities for the making of electronic deeds by Land Deed Officials (PPAT), yet it raises juridical issues due to the use of the term “may,” which creates uncertainty regarding which types of deeds are permitted and what format of electronic deeds is legally valid. On the one hand, this regulation represents progress toward the digitalization of land services and has the potential to improve public service efficiency. On the other hand, the absence of specific provisions governing electronic face-to-face procedures, deed reading mechanisms, and system security standards presents serious challenges to implementation. This study employs a doctrinal juridical method by examining relevant regulations, including PP 18/2021, PP 71/2019, Ministry of Agrarian Affairs and Spatial Planning/National Land Agency Regulation (Permen ATR/BPN) No. 20/2021, and Permen ATR/BPN No. 3/2019, supported by interviews with PPAT. The findings indicate that the implementation of electronic deeds by PPAT will inevitably take place sooner or later; however, the current lack of regulatory clarity has the potential to hinder legal certainty. Therefore, the establishment of specific regulations governing technical procedures, electronic system standards, and legal protection is crucial to ensure that the implementation of electronic deeds not only provides efficiency opportunities but also guarantees legal certainty for all parties. Keywords: Electronic Deeds, PPAT, Legal Certainty, PP 18/2021